Kentucky Foreign Language Quarterly. University of Kentucky at Lexington: tomo 1 (1954), tomo 2 (1955). - M. A. Vergara (Nueva Revista de Filología Hispánica, 1957)
Se reseñó: Kentucky Foreign Language Quarterly: tomo 1 (1954), tomo 2 (1955).